2016
DOI: 10.1161/strokeaha.116.013418
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds and Cortical Superficial Siderosis in Patients Presenting With Minor Cerebrovascular Events

Abstract: Background and Purpose-Transient focal neurological episodes occur in cerebral amyloid angiopathy (CAA) and can mimic transient ischemic attack (TIA). Risk factors and outcomes of minor ischemic stroke or TIA might differ in patients with and without cerebral microbleeds (CMBs), including CAA-consistent lobar CMB. Methods-Baseline magnetic resonance imaging (MRI) was analyzed for CMBs and cortical superficial siderosis in 416 patients in the prospective computed tomography and MRI in the CATCH study (Triage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Similarly, neuroimaging may enhance the prognostic ability following TIA and minor stroke. However, recent analyses of patients with TIA or minor IS show that white matter lesions are associated with disability at 90 days, but not with stroke progression or stroke recurrence [6], and micro bleeds predict neither 90-day outcome or recurrence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, neuroimaging may enhance the prognostic ability following TIA and minor stroke. However, recent analyses of patients with TIA or minor IS show that white matter lesions are associated with disability at 90 days, but not with stroke progression or stroke recurrence [6], and micro bleeds predict neither 90-day outcome or recurrence [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer data on the proportion of possible TIA that may instead be CAA-related TFNEs. In one prospective study of patients with possible ischemic symptoms who were consecutively consented to undergo MRI, 4/416 (1.0%) were retrospectively assessed as having CAA-related TFNEs 50 . Thus, current evidence suggests that most non-traumatic cSAH in the elderly, three quarters of cSS, and 1% of suspected TIA cases may be related to CAA.…”
Section: Incidence Of Caa-related Tfnesmentioning
confidence: 99%
“…Because we did not do a prospective study, we cannot give an accurate prevalence for CAA-associated cSAH in a TIA clinic as not all TIA clinic patients in the control group underwent imaging if it was not clinically indicated. However, one recent paper suggested that this might be around 1% [8]. Our sample size remains small, with wide confidence intervals around the odds ratios for each presenting symptom.…”
Section: Discussionmentioning
confidence: 75%